(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
In this article the regularities of colouristics of the novels «The Evil» by L. Bagrat, «The Persecutor of Clouds» by Dara Korniy, «Buretsvit» by M. Ryapolova, and «Mantra-omana» by V. Granetskaya are analysed. It is discovered the logic of used of coloratives comparatively of these works genre nature, principles of its plot deployment, and also of the specific authors’ accents. It is shown, that the colouristics system plays special role in modeling of the analysed novels mythspace.